La construcción de imaginarios urbanos a través de la fotografía de edificaciones patrimoniales del Centro Histórico de Riobamba, años 20- actualidad - Salazar Salazar, María Fernanda (2018)
The present investigation has as purpose the analysis of the construction of the urban imaginaries, through the photograph of Patrimonial Buildings of the Historical Center of Riobamba 20 years - present. This project is based on the following communicational theories: Moles structuralist, who bases his theory on man as an individual deeply related to his environment and Visual Anthropology, which encompasses the study of all visual and graphic forms of culture, as well as as well as the production of visual material (photography), where objects and actions are produced with the intention of communicating something to someone. It is important to mention that the Historical Center is a place of recognition for people, this is where significant representations of a city are born. The subject raises an aspect of study that uses the photographic document and its circulation in different iconographic contents. The methodology used focuses on the descriptive and comparative methods, we worked with a stratified sample of the inhabitants of urban Riobamba; Surveys, interviews, photo essays and comparative photographs were applied. In the survey applied 92% of people consider that the photography of heritage buildings helps to evidence the past, to be compared with the present. So it is concluded that through photography can be seen the significant changes that the city has had over time, and how these have influenced the representations that the inhabitants make of their city.